2015
DOI: 10.1007/s00484-015-1103-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of a mixture of Lactobacillus strains enhances performance of broiler chickens raised under heat stress conditions

Abstract: High ambient temperature is a major problem in commercial broiler production in the humid tropics because high producing broiler birds consume more feed, have higher metabolic activity, and thus higher body heat production. To evaluate the effects of two previously isolated potential probiotic strains (Lactobacillus pentosus ITA23 and Lactobacillus acidophilus ITA44) on broilers growing under heat stress condition, a total of 192 chicks were randomly allocated into four treatment groups of 48 chickens each as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 53 publications
5
35
0
Order By: Relevance
“…SGLT-1 mediates Na + -dependent glucose absorption across the luminal membrane of animal enterocytes, which is the major route for the utilisation of dietary sugars [42]. It was reported that probiotic addition increased some types of intestinal nutrient transporters in broilers [43]. An in vitro study revealed that S .…”
Section: Discussionmentioning
confidence: 99%
“…SGLT-1 mediates Na + -dependent glucose absorption across the luminal membrane of animal enterocytes, which is the major route for the utilisation of dietary sugars [42]. It was reported that probiotic addition increased some types of intestinal nutrient transporters in broilers [43]. An in vitro study revealed that S .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of probiotics (Lactobacillus rhamonus and Lactococcus lactis) into the mouse diet increased the expression of the FABP4 gene (Suzuki et al, 2017). On the other hand, the addition of probiotics to the broiler chicken diet results in the higher expression of GLUT2, which is related to the increased glucose uptake (Faseleh Jahromi et al, 2016). The studies examining the effect of mixed probiotics on epithelial cells (in particular:…”
Section: Gene Expressionmentioning
confidence: 99%
“…can be effective methods. As reported, Bacillus licheniformis might be useful for ameliorating the adverse influence of heat on the egg production and gut health of laying hens [6], Lactobacillus improved the average daily gain (ADG) of broilers [7], methionine hydroxy analogue alleviated major damage of broilers through the action on some genes related to thioredoxin complex activity [8], and organic acid improved microbiological quality of chicken meat [9]. Numerous studies have reported that dietary organic acid or organic acid salts can improve the growth performance, immune status and gut health of broilers [10,11].…”
Section: Introductionmentioning
confidence: 90%